(untitled) (Indonesian Tourism Justice Review, 2025)
Global tourism corporations play a dominant role in shaping the economic landscape of tourist destinations in Indonesia, yet the economic benefits of international tourism often fail to reach local communities. This paper critically assesses the impact of globalization on local economies in Indonesia, focusing on how international tourism chains (hotels, resorts, airlines) contribute to economic disparities. Through case studies of regions like Bali, Jakarta, and Yogyakarta, the research examines how these multinational corporations control key aspects of the tourism value chain, from accommodations to transportation, leaving local businesses with limited economic opportunities. The study explores issues such as the leakage of tourism revenue, labor exploitation, and the marginalization of small local enterprises. The paper also evaluates government policies that aim to redistribute tourism benefits more equitably, proposing reforms to ensure that tourism contributes to long-term economic justice. It calls for stronger regulations that promote local ownership, fair wages, and sustainable tourism practices that prioritize the economic interests of local communities.